Evaluation of agreement between invasive and non-invasive blood pressure measurement using the PetMAP™ device in rabbits - Sredenšek, Jerneja; Žel, Jurij; Rocchi, Attilio; Gasparik-Küls, Nina (Frontiers in Veterinary Science, 2023)
Background: Measurement of arterial blood pressure recommended in anaesthetized animals to guide perioperative treatment. Invasive blood pressure measurement is considered the gold standard, however it is also technically challenging, requires specialized equipment and carries certain risks. For these reasons, non-invasive blood pressure measurement devices are commonly used and are expected to provide accurate and reliable results. This requirement is particularly true for rabbits, in whom peri-anaesthetic hypotension is commonly observed and in whom perioperative mortality remains disproportionally high. Several authors have compared different non-invasive devices with invasive measurements in rabbits and have reported contrasting results. However, to date no comparison between invasive measurements and the PetMAP TM device, that has been designed specifically for veterinary medicine, has been reported.Aim & Hypothesis: The aim of the study was the comparison of invasive blood pressure measurement with PetMAP TM in rabbits. We hypothesized that PetMAP TM would show acceptable agreement with the invasive measurements according to the American College of Veterinary Internal Medicine guidelines.Materials & methods: Sixteen client-owned rabbits presenting for various surgical interventions were included in the study. Invasive measurements were performed by cannulation of an auricular artery. The PetMAP TM cuff was applied distal to the elbow according to the manufacturer's guidelines. For each measurement with PetMAP TM , three invasive blood pressure values were recorded. The mean of the three invasive values was compared with one value measured with PetMAP TM .Results: Data collected from 16 rabbits were used for statistical analysis. In the clinical setting, the PetMAP TM device showed significant overestimation of systolic, diastolic and mean arterial pressure, which were measured in the auricular artery. In addition, the bias was not constant, implying that the device poorly predicted changes in blood pressure. Conclusion: The PetMAP TM device did not meet any of the American College of Veterinary Internal Medicine recommendations. Number of tables: 3 Number of figures: 3